2005
DOI: 10.1111/j.1468-2982.2005.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity is Impaired in Patients with Migraine

Abstract: Several studies have shown the presence of a comorbidity between migraine and vascular diseases, like hypertension and stroke. The mechanisms of this comorbidity are unknown. Impaired insulin sensitivity has recently emerged as a risk factor for hypertension and stroke. We evaluated insulin sensitivity in 30 young, nonobese, nondiabetic, normotensive migraine patients and in 15 healthy controls. During the OGTT, glucose plasma concentrations were significantly higher in migraineurs than in controls. Insulin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
103
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 23 publications
11
103
2
Order By: Relevance
“…Migraine is a disease with a presumed vascular mechanism. 3 Recently, several epidemiologic, longitudinal, case-control, and cohort studies demonstrated association between migraine and vascular risk comorbid medical conditions including: increased body mass index (BMI) or obesity, 4 hypercholesterolemia/dyslipidemia, 5 hypertension, 6 impaired insulin sensitivity, 7 ischemic stroke in young adults, 8 and coronary heart disease. 9 These associations or comorbidities are not explained by bias.…”
mentioning
confidence: 99%
“…Migraine is a disease with a presumed vascular mechanism. 3 Recently, several epidemiologic, longitudinal, case-control, and cohort studies demonstrated association between migraine and vascular risk comorbid medical conditions including: increased body mass index (BMI) or obesity, 4 hypercholesterolemia/dyslipidemia, 5 hypertension, 6 impaired insulin sensitivity, 7 ischemic stroke in young adults, 8 and coronary heart disease. 9 These associations or comorbidities are not explained by bias.…”
mentioning
confidence: 99%
“…[3][4][5][6] Sphingolipids (e.g., sphingomyelins, ceramides) are a group of bioactive lipids that are critical components of membrane microdomains. 7,8 In addition to important structural roles, these…”
Section: Classification Of Evidencementioning
confidence: 99%
“…Moreover, Okada et al [816] demonstrated higher levels of lactic acid and pyruvic acid in the plasma of patients with migraine as compared with controls, which indicated mitochondrial function abnormalities in carbohydrate and fats metabolism, including tricarboxylic acid cycle. In addition, insulin sensitivity was found to be impaired in the patients with migraine as compared with normal individuals (P < 0.001) [817,818]. Therefore, its seems that there is a relationship between migraine/other types of headache and T1DM/T2DM, especially that many patients with recurrent headaches/migraine were found to be seropositive for T. gondii [819,820] and about two billion of people worldwide are chronically infected with the parasite.…”
Section: Possible Association Between Diabetes Migraine/other Type Omentioning
confidence: 98%